Ship damage stability approval document generation by a Monte Carlo method - Krüger, Stefan; Aschenberg, Katja (Volume 6: Ocean Engineering, 2021)
The revised SOLAS 2020 damage stability regulations have a strong impact on possible future ship designs. To cope with these requirements, damage stability investigations must become a central part of the initial design phase, and many internal subdivision concepts need to be investigated. Unfortunately, if damage stability calculations are performed in the classical way, they are very time consuming with respect to modelling and computational time. This fact has impeded the consequent subdivision optimization in the past. Therefore, a simulation procedure for damage stability problems was developed which treats damage stability as a stochastic process which was modeled by a Monte Carlo simulation. If statistical damage distributions are once known, the Monte Carlo simulation delivers a population of damages which can be automatically related to certain damage cases. These damage cases can then be investigated with respect to their survivability. Applying this principle to damage stability problems reduces the computational effort drastically where at the same time no more manual modelling is required. This development does especially support the initial design phase of the compartmentation and leads to a safer and more efficient design. If this very efficient simulation principle shall now also be used after the initial design phase for the generation of approval documents, additional information needs to be generated by the simulation method which is not directly obtained during the simulation: This includes detailed individual probabilities in all three directions and the integration of all damage cases into predefined damage zones. This results in fact in a kind of reverse engineering of the manual damage stability process to automatically obtain this required information. It can be demonstrated that the time to obtain the final documents for the damage stability approval can be drastically reduced by implementing this principle.